Freedom under the Key: Models of Discipline and Punishment of Queer Masculinity in the Novels Our Lady of the Flowers by Jean Genet and Brother by David Albahari - Perišić, Igor (Porównania, 2016)
This paper, based on an idea of Michel Foucault from the book Discipline and Punishment, examined how the repressive systems of discipline and punishment are present in selected literary works: on the concrete levels in the novel Our Lady of the Flowers by French author Jean Genet, and on the symbolic levels in the novel Brother by Serbian writer David Albahari, primarily in relation to the moved, queer masculinity, or more precisely the transvestite or transgender persons. At the same time, attention was given to the figure of male friendship, or androcentric figure as the basis of Western philosophy and theory, the figure that excludes heterosexual friendship and friendship among women, as described by Jacques Derrida in his book The Politics of Friendship.